Technology Selection for Removal of PFAS from Raw Water for Drinking Water Purposes - Hansson , Frida; Wu, Lisa (My University, 2024)
Per- and polyfluoroalkyl substances (PFAS) are a synthetic group of chemicals that can be harmful for humans and the environment. The use of PFAS has caused the presence of it in drinking water. Two thirds of the groundwater sources in Sweden have found to be contaminated with PFAS. To limit PFAS in drinking water, the European Food Safety Authority, EFSA, has introduced a guideline of 4 ng/L for PFAS 4 and 100 ng/L for PFAS 21 which will be implemented 2026. This study investigates technical and sustainability performance of the technologies Granular Activated Carbon (GAC), Nanofiltration (NF), Ion Exchange (IX) and Foam Fractionation (FF). The study has been performed through a literature study with help from databases such as Web of Science using search strings. The results were presented in a flowchart and a table with results from the sustainability performance analysis. Granular activated carbon and IX alone or in combination with each other or other technologies were to be suggested in the majority of the cases. Nanofiltration showed to have high performance in many aspects, including for short-chained PFAS, with a disadvantage of highly concentrated waste stream that needs further treatment. Foam fractionation needs specific conditions for proper performance but is not suitable for drinking water treatment purposes.
Keywords: PFAS; nanofiltration; granular acitvated carbon; foam fractionation; ion exchange; operation and maintenance cost; decision-support; drinking water; water treatment